Quality Pedagogical Practice in Early Childhood Education Institutions Relating to Children at Risk of Social Exclusion - Sandra Antulić Majcen; Maja Drvodelić (Center for Educational Policy Studies Journal)
Quality early childhood education and care has been the focus of interest of researchers for over half a century. Approaches to the quality monitoring and quality assurance of early childhood education and care, as well as its conceptualisation and operationalisation, have changed and developed over the decades in line with contemporary understandings of child development and learning, and in accordance with changes in the purpose and functions of early childhood education and care. The results of many relevant studies confirm that quality early childhood education and care is crucial for short-term and long-term positive outcomes in different development and learning areas, especially in the case of disadvantaged children, including children at risk of social exclusion. The aim of this paper is to present the concept of quality in early childhood education and care from various research perspectives, with special emphasis on a review of the literature on the quality of pedagogical practice aimed at children at risk of social exclusion. The paper presents the theoretical model of responding to the needs of children at risk of social exclusion in Croatian early childhood education and care. Special attention is given to the quality of pedagogical practice regarding children at risk of social exclusion, as a prerequisite for planning targeted measures and interventions directed at this group of children and their families within the Croatian early childhood education and care system. It was concluded that the key factors for quality pedagogical practice are an interdisciplinary approach of highly qualified professionals and the participation of all key stakeholders within the child’s immediate environment, as well as connection between relevant policies and practice, which are crucial for early childhood education and care quality.